Upaya Mencegah Penyebaran Covid-19 dengan Penyuluhan Mencuci Tangan serta Memakai Masker - Rofiatun Nisa’; Zainal Muslikhin (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
Handling Covid-19 must be carried out thoroughly and involve all parties from various walks of life by applying health protocols, which are continuously being pursued to deal with the spread of Covid-19 by always practicing hand hygiene by washing hands with soap and using masks. This service aims to provide counseling to students at MI Ta'limul Huda Bugoharjo how to wash hands and wear masks properly. Community service is carried out for 1 month, namely in August 2020 using a one-by-one or interpersonal counseling approach by way of home visits to each student's home and practicing it directly. Based on the results of the service carried out to students about counseling on washing hands using soap and masks, it was found that students were very happy and enthusiastic in participating in the counseling provided and practicing directly in washing hands and wearing masks.